Notch and Wingless Regulate Expression of Cuticle Patterning Genes - Wesley, Cedric Satish (American Society for Microbiology, 1999)
The cell surface receptor Notch is required during Drosophila embryogenesis for production of epidermal precursor cells. The secreted factor Wingless is required for specifying different types of cells during differentiation of tissues from these epidermal precursor cells. The results reported here show that the full-length Notch and a form of Notch truncated in the amino terminus associate with Wingless in S2 cells and in embryos. In S2 cells, Wingless and the two different forms of Notch regulate expression of Dfrizzled 2, a receptor of Wg; hairy, a negative regulator of achaete expression; shaggy, a negative regulator of engrailed expression; and patched, a negative regulator of wingless expression. Analyses of expression of the same genes in mutant N embryos indicate that the pattern of gene regulations observed in vitro reflects regulations in vivo. These results suggest that the strong genetic interactions observed between Notch and wingless genes during development of Drosophila is at least partly due to regulation of expression of cuticle patterning genes by Wingless and the two forms of Notch.